2022
DOI: 10.1007/s11356-022-21267-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tetracycline on the secondary metabolites and nutritional value of oilseed rape (Brassica napus L.)

Abstract: Secondary metabolism, which helps a plant cope with external stress, is sensitive to environmental changes and plays a prominent role in maintaining plant health. However, few studies of the effects of tetracycline on the relationships between secondary metabolism and plant stress responses have been performed. Here, secondary metabolism, nutritional value, and oxidative stress responses in oilseed rape (Brassica napus L.) exposed to tetracycline for 14 d were investigated. Tetracycline inhibited growth and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Excessive reactive oxygen species (ROS) are produced during the growth of oilseed rape seedlings under antibiotic exposure (Zhao et al, 2023), and aerobic metabolism and pollution stress during seed development and formation also produce harmful ROS (Bailly, 2004). There were changes in the relative content of ROS in oilseed rape seeds with TC and SMZ, as shown in Figs.…”
Section: Effect Of Tc and Smz On Ros Content Of Oilseed Rape Seedsmentioning
confidence: 94%
See 1 more Smart Citation
“…Excessive reactive oxygen species (ROS) are produced during the growth of oilseed rape seedlings under antibiotic exposure (Zhao et al, 2023), and aerobic metabolism and pollution stress during seed development and formation also produce harmful ROS (Bailly, 2004). There were changes in the relative content of ROS in oilseed rape seeds with TC and SMZ, as shown in Figs.…”
Section: Effect Of Tc and Smz On Ros Content Of Oilseed Rape Seedsmentioning
confidence: 94%
“…Rapeseed is rich in secondary metabolites such as avonoids, carotenoids and tocopherols, which promote human health, and also improve the quality of rapeseed and prolong its storage period (Shen et al, 2023). Recent studies have demonstrated that stresses from antibiotic and heavy metal pollution have signi cant effects on secondary metabolism and antioxidant effects in hydroponically grown rapeseed seedlings (Zhao et al, 2023, Skhawat et al, 2018, but little is known about the effects of antibiotic exposure throughout the growth cycle on rapeseed seed quality and oxidative stress have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[50,51,52,53,54] Polyketides include a series of natural products with complex structure, such as macrolides, polyenes, anthraquinones, naphthalene, flavonoids, tetracycline and so on. [55,56,57,58] Due to the great application value of these compounds in antimicrobial, anti-tumor, anti-infection, etc., researchers are attracted to carry out in-depth and systematic research on polyketides. The antimicrobial activities of polyketides from marine Penicillium spp.…”
Section: Polyketides Derived From Marine Penicillium Spp and Their An...mentioning
confidence: 99%
“…The leaf growth and the characteristics of secondary metabolites are critically significant for the quality control and production of plants [ 1 ]. Secondary metabolism assists a plant to cope with environmental factors, is sensitive to external changes, and performs a vital role in sustaining plant growth [ 2 ]. In addition, these also can promote plant growth due to preventing the disease by redeeming vegetative growth by the increase of root and shoot systems production [ 3 ].…”
Section: Introductionmentioning
confidence: 99%